ANALISIS FENOMENA UNDERPRICING INITIAL PUBLIC OFFERING PADA KELOMPOK PERUSAHAAN KEUANGAN DAN NON-KEUANGAN DI BURSA EFEK JAKARTA - Dewi, Sandra (jurnal ekonomi, 2007)
Underpricing is an indication that there is a too low price determination on the prime stock emition and couses an abnormal return when it is first traded in the investor secondary market. When buying the prime stock, the investor is able to enjoy the capital gain at the time that stock is sold in the secondary market. The samples which are used in this research are about 96 company samples. From this research, it is shown that there is no underpricing phenomenon in the Jakarta Stock Exchange prime market which is indicated before by the negative prime abnormal return avarage and statistically significant. The later result proves that the average of the prime abnormal return in the financial group is smaller than the average of the prime abnormal return in the non-financial group. The emition guarantor reputation has a negative influence but it is not statically significant, offer size shows the positive influence over the underpricing and it is not statistically significant on the level 10% alpha. And by using the LOGHL deviation standar, the stock valotility does not show a significant effect on the 10% level dad has a positive influence with hte underpricing.